THE PRESENCE OF BARK IN Acacia mangium WOOD IMPROVES ITS ENERGETIC POTENTIAL - Sette Jr, Carlos Roberto; Souza, Brenda Rodrigues de; Coneglian, Ademilson; Moraes, Mariana Dianese Alves de; Barboza, Frederico Severino (Floresta, 2020)
The use of the wood associated with the bark of forest species for energy purposes can be a viable alternative from the technical, environmental and economic points of view. The objective of this study was to evaluate the effect of maintaining the bark on the energetic characteristics of Acacia mangium and Eucalyptus urophylla x Eucalyptus grandis (urograndis) wood and briquettes. Trees of both species of 7 years old were cut from field experiments and wood samples with and without bark were obtained to evaluate the physical and energetic characteristics of the biomass and briquettes. The presence of bark in A. mangium wood improved the energetic characteristics of the biomass, and its use in small quantities together with wood for energy applications is technically feasible. Maintaining the bark in small quantities in the Urograndis wood promoted a reduction in the energetic characteristics of the biomass. The characteristics of the briquettes were not influenced by the species or the presence of bark in the wood.